INOVASI PEMBELAJARAN KEMUHAMMADIYAHAN DALAM PENGEMBANGAN METODE DAN STRATEGI PENDIDIKAN ISLAM - Arisnelwati, Arisnelwati; Oktavia, Risna; Syakban, Ismail (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to explore the concept and model of innovation in the learning of Kemuhammadiyahan as an effort to improve the quality of Islamic education in Muhammadiyah schools. Using a qualitative-descriptive approach, data were collected through literature studies and documentation of various educational practices within Muhammadiyah institutions. The findings show that learning innovation in Kemuhammadiyahan integrates technological development, contextual learning, and value-based education. Models such as Project-Based Learning, Problem-Based Learning, and Blended Learning have been proven effective in fostering students' critical thinking, social awareness, and Islamic character. The study concludes that innovation in Kemuhammadiyahan learning not only improves cognitive aspects but also internalizes Islamic progressive values in students' daily lives.Keywords: Islamic education; Muhammadiyah; innovation; learning strategy; value-based learning